Curvature-enhanced membrane asymmetry slows down protein diffusion - Kumar, Jatin (2024)
Diffusion of transmembrane proteins plays a vital role in various cellular processes, such as endocytosis, raft formation and signal transduction. Current understanding of protein diffusion dynamics in lipid membranes is mostly based on hydrodynamic analyses, in which lipid membrane is simply treated as a thin layer of viscous liquid, same for highly curved ones. Therefore, how the mechanical state of highly curved membranes may affect the transmembrane protein diffusion remains unclear. In this study, we employed molecular dynamics (MD) simulations to analyse membrane curvature effect on the diffusion of cylindrically shaped Aquaporin-0 (AQP0) protein. Slowing down of protein diffusion with the increase in membrane curvature was observed. The possible contributions from membrane tension and asymmetric pressure profile were systematically investigated by simulating the protein diffusion dynamics in planar membranes with various tension levels or with various lipid number ratios between the two leaflets, respectively. We found no significant effect of membrane tension on AQP0 diffusion. Instead, the asymmetric pressure profile present in highly curved bilayer membranes was identified as a key factor that contributes to the slowing down of transmembrane protein diffusion. Our work thus contributes to a more complete picture of transmembrane protein diffusion on highly curved biological membranes.